UJI EFEKTIVITAS EKSTRAK DAUN BINAHONG (Anredera Cordifolia) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS - Nin Suharti (Poltekkes Kemenkes Medan, 2022)
Binahong is one of the plants that can treat various types of diseases, especially infectious diseases. Infectious diseases are the main cause of high morbidity and mortality, especially in developing countries such as Indonesia and the most common is Staphylococcus aureus. Binahong plant (Anredera cordifolia) is a potential medicinal plant that can overcome various types of diseases and has inhibitory power against bacteria. This study aims to determine the effectiveness of binahong leaf extract against the growth of Staphylococcus aureus bacteria by measuring the inhibition zone formed. The materials used are binahong leaf extract and Staphylococcus aureus bacteria. This type of research is experimental using disc paper with levels of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. In Muller Hinton media for the growth of Staphylococcus aureus bacteria, the diameter of the inhibition zone formed was measured. The results showed that the highest value of the inhibition zone of the binahong leaf extract was at a concentration of 80% with an inhibitory zone of 9.78 and the lowest was at a concentration of 10% with an inhibitory zone of 8.63. The effectiveness of the best binahong leaf extract in inhibiting the growth of Staphylococcus aureus bacteria is at a concentration of 80%. This indicates that the binahong leaf extract has an antibacterial effect against Staphylococcus aureus bacteria.Abstrak